2014
DOI: 10.4103/0973-7847.125525
|View full text |Cite
|
Sign up to set email alerts
|

A current update on the phytopharmacological aspects of Houttuynia cordata Thunb

Abstract: The present review is an attempt to put an insight into a medicinal plant Houttuynia cordata Thunb, which is indigenous to North-East India and China. It is an aromatic medicinal herb belonging to family Saururaceae and is restricted to specialized moist habitats. The review provides detailed information regarding the morphology, distribution, phytochemistry, ethnopharmacological uses and also describes various pharmacological activities reported on the plant H. cordata. The review describes therapeutic effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 33 publications
1
48
0
Order By: Relevance
“…These data are in agreement with the findings of Duan (1998) who proposed that in fish as in mammals, IGF-I plays a central role in the hormonal control of growth. However, H. cordata has been shown to possess anti-hyperglycaemic activity and promote the insulin secretion in rodents (Kumar et al, 2014). Kumar, Prasad, and Hemalatha (2016) reported that H. cordata plant consists of flavonoid compounds mainly quercetin that has potent ability to induce the secretion of insulin and finally that up-regulate the IGF-I expression.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in agreement with the findings of Duan (1998) who proposed that in fish as in mammals, IGF-I plays a central role in the hormonal control of growth. However, H. cordata has been shown to possess anti-hyperglycaemic activity and promote the insulin secretion in rodents (Kumar et al, 2014). Kumar, Prasad, and Hemalatha (2016) reported that H. cordata plant consists of flavonoid compounds mainly quercetin that has potent ability to induce the secretion of insulin and finally that up-regulate the IGF-I expression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that an ethnomedicine named as Bragen (prepared from Bergenia stracheyi as well) was also used for the treatment of arthritis. Recently in 2014, Kumar et al reported that the extracts of Houttuynia cordata can be used for the healing of hemorrhoids, and this species is frequently used in tradtional Tibetan and Chinese medicines [20]. We found that the ethnomedicine Maraptang prepared from Houttuynia cordata were also used by the tradtional Monpa healers for the treatment of piles which is a type of hemorrhoid.…”
Section: Discussionmentioning
confidence: 87%
“…Many phytochemical compounds in both plants have been reported, such as phenolic acids and alkaloids [7,8]. We investigated the total phenolic acid contents, flavonoids and antioxidant activity, as shown in Table 1.…”
Section: Identification Of Phytochemical Compositions In H Cordata Amentioning
confidence: 99%
“…There is a long history of herbal medicine plants widely distributed in East Asia, with Chinese people having utilized herbs and plants to treat various diseases for a long time. Moreover, they are intriguing natural products which are widely used as food supplements and to promote health [7]. Furthermore, H. cordata possesses anti-cancer, anti-diabetics, and anti-inflammation properties.…”
Section: Introductionmentioning
confidence: 99%